Parallel processing of face and house stimuli by V1 and specialized visual areas: a magnetoencephalographic (MEG) study - Shigihara, Yoshihito; Zeki, Semir (Frontiers in Human Neuroscience, 2014)
We used easily distinguishable stimuli of faces and houses constituted from straight lines, with the aim of learning whether they activate V1 on the one hand, and the specialized areas that are critical for the processing of faces and houses on the other, with similar latencies. Eighteen subjects took part in the experiment, which used magnetoencephalography (MEG) coupled to analytical methods to detect the time course of the earliest responses which these stimuli provoke in these cortical areas. Both categories of stimuli activated V1 and areas of the visual cortex outside it at around 40 ms after stimulus onset, and the amplitude elicited by face stimuli was significantly larger than that elicited by house stimuli. These results suggest that "low-level" and "high-level" features of form stimuli are processed in parallel by V1 and visual areas outside it. Taken together with our previous results on the processing of simple geometric forms (Shigihara and Zeki, 2013, 2014), the present ones reinforce the conclusion that parallel processing is an important component in the strategy used by the brain to process and construct forms.